Seasonality in schizophrenia—An analysis of a nationwide registry with 110, 735 hospital admissions. Issue 1 (2020) - Hinterbuchinger, B.; König, D.; Gmeiner, A.; Listabarth, S.; Fellinger, M.; Thenius, C.; Baumgartner, J. S.; Vyssoki, S.; Waldhoer, T.; Vyssoki, B.; Pruckner, N.
Abstract: Background: Seasonal patterns in hospitalizations have been observed in various psychiatric disorders, however, it is unclear whether they also exist in schizophrenia. Previous studies found mixed results and those reporting the presence of seasonality differ regarding the characteristics of these patterns. Further, they are inconclusive whether sex is an influencing factor. The aim of this study was therefore to examine if seasonal patterns in hospitalizations can be found in schizophrenia, with special regard to a possible influence of sex, by using a large national dataset. Methods: Data on all hospital admissions within Austria due to schizophrenia (F20.0–F20.6) for the time period of 2003–2016 were included. Age standardized monthly variation of hospitalization for women and men was analyzed and the level of significance adjusted for multiple testing. Results: The database comprised of 110, 735 admissions (59.6% men). Significant seasonal variations were found in the total sample with hospitalization peaks in January and June and a trough in December ( p < 0.0001). No significant difference in these patterns was found between women and men with schizophrenia ( p < 0.0001). Conclusion: Our study shows that schizophrenia-related hospitalizations follow a seasonal pattern in both men and women. The distribution of peaks might be influenced by photoperiod changes which trigger worsening of symptoms and lead to exacerbations in schizophrenia. Further research is necessary to identify underlying factors influencing seasonal patterns and to assess whether a subgroup of patients with schizophrenia is especially vulnerable to the impact of seasonal variations.